As práticas políticas de Silvestre Rebello: um diplomata brasileiro nos Estados Unidos da América (1824-1829) - Cruz, Abner Neemias da [UNESP] (2015)
At the time of the first reign, Silvestre Rebello was the Brazilian diplomat representing the Brazilian Government in the United States. This job aims to understand the politic actions of Rebello during the years of 1824 to 1829 including the specific matters involved in the established relation between Brazil and USA. This |Master's Thesis also intends to think about the Rebello actions and the institutional relations between the Brazilian Foreign Business Agency and the American Government and the public opinion about it. To get these objects, it is going to use the letters sent and receipt by Rebello and the Brazilian Foreign Business Agency in the years of 1824 to 1829 and also the official documents produced by the Brazilian and American agencies and the running newspapers.